2020
DOI: 10.3390/w12010164
|View full text |Cite
|
Sign up to set email alerts
|

Hydrologic Responses to Climate Variability and Human Activities in Lake Ziway Basin, Ethiopia

Abstract: Hydrological impacts of human activities and climate variability on Ketar and Meki watersheds of Lake Ziway basin, Ethiopia were studied using the soil and water assessment tool. Three land-use change and two climate variability scenarios were considered to analyze the separate and combined impacts on annual water balance, monthly streamflow, and spatial distributions of evapotranspiration and water yield. The evaluation showed that changes in land use resulted in an increase in annual surface runoff and water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 63 publications
(68 reference statements)
0
21
0
Order By: Relevance
“…They also documented that reduction in runoff has been caused by decrease in rainfall and increase in temperature. Furthermore, other studies found that an annual decline in Ziway Lake water level is due to a decrease in runoff from both the Katar and Meki rivers, including increase in evapotranspiration from the basin [20,21]. These studies show that water resources of the ZLB are highly exposed to a rapidly changing global climate [22].…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations
“…They also documented that reduction in runoff has been caused by decrease in rainfall and increase in temperature. Furthermore, other studies found that an annual decline in Ziway Lake water level is due to a decrease in runoff from both the Katar and Meki rivers, including increase in evapotranspiration from the basin [20,21]. These studies show that water resources of the ZLB are highly exposed to a rapidly changing global climate [22].…”
Section: Introductionmentioning
confidence: 70%
“…The Central Rift Valley (CRV) Lakes Basin of Ethiopia, located in the eastern part of the country, has experienced considerable seasonal and annual rainfall variability, with a prominent increase in temperature [19]. Some studies have already documented the hydroclimate conditions and climate change impacts in the CRV, including partially in the Ziway Basin (Meki and Katar sub-basins, the two major sub-basins draining into the Ziway Lake) [20,21]. For example, Musie et al [21] have reported climate variability has negatively impacted the monthly streamflow of the Ziway Lake Basin (ZLB).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Soil erosion, worsen by land use/ land cover (LU/LC) change is the most common form of land degradation that covers 23% of Ethiopia (Gebreselassie et al 2016). A gradual change in LU/LC features was observed sourced from demographic changes, poverty, topography, and land policy those are contributing to environmental changes such as biodiversity loss, soil erosion, local climate, and hydrological regime (Desta and Fetene 2020; Musie et al 2020;Woldesenbet et al 2020).…”
Section: Introductionmentioning
confidence: 99%